Calcium-Dependent Protein Kinase GhCDPK28 Was Dentified and Involved in Verticillium Wilt Resistance in Cotton - Wu, Yajie; Zhang, Lei; Zhou, Jinglong; Zhang, Xiaojian; Feng, Zili; Wei, Feng; Zhao, Lihong; Zhang, Yalin; Feng, Hongjie; Zhu, Heqin (Frontiers in Plant Science, 2021)
Verticillium dahliae (V. dahliae) is a soil-borne fungus that causes vascular wilt through the roots of plants. Verticillium wilt caused by V. dahliae is the most destructive cotton crop diseases in some parts of the world. Average losses due to attack of this disease are tremendous every year. Breeding resistant varieties is the most economical and effective method to control Verticillium wilt. We identified a Calcium-dependent Protein kinase GhCDPK28 from upland cotton (Gossypium hirsutum) and characterized its functional mechanism. In previous studies, we found phosphorylation of threonine 13, 14 and 15 in GhCDPK28 through proteomic analysis of cotton roots infestation by V. dahliae. In this study, knockdown of GhCDPK28 expression, the content of reactive oxygen species was increased, a series of defense responses were enhanced, and the sensitivity of cotton to dahlia was reduced. Moreover, overexpression of GhCDPK28 in Arabidopsis thaliana weakened the resistance of plants to this pathogen. Subcellular localization in Nicotiana benthamiana showed that GhCDPK28 was localized in the cell membrane, and phosphorylation site mutation alters its localization. We also found two proteins that may interact with GhCDPK28. These results indicate that GhCDPK28 is a potential molecular target for improving resistance to Verticillium wilt in cotton. This lays a foundation for breeding disease-resistant varieties.